Motivasi Petani dalam Budidaya Tanaman Jagung Manis untuk Meningkatkan Kesejahteraan Pendapatan Petani di Kecamatan Senggi, Kabupaten Keerom - Yan Piter Ulop; Eko Harianto; Eksa Rusdiyana (Universitas Sebelas Maret, 2025)
Farmers’ Motivation in Sweet Corn Cultivation to Improve Farmers’ Income Welfare in Senggi Sub-District, Keerom Regency. Senggi Sub-district, Keerom Regency, has significant potential in the promising sweet corn commodity. However, farmers’ motivation in sweet corn cultivation is still constrained by several factors, such as income, land size, and social environment. This study aims to analyze farmers’ motivation in sweet corn cultivation and its relationship with the improvement of farmers’ income welfare in Senggi Sub-district, Keerom Regency. The research employed a quantitative descriptive method with a population of 200 farmers, from which 60 respondents were selected using proportional random sampling. Data were collected through questionnaires, in-depth interviews, and documentation, then analyzed using interval width tests and Spearman’s rank correlation. The results indicate that farmers’ motivation is dominated by the need for livelihood sustainability, with 51.67% of respondents categorized as very high. Age does not have a significant effect on motivation, whereas non-formal education, land size, number of family members, income, and social environment were found to have a positive and significant relationship with farmers’ motivation. In contrast, the economic environment showed no significant relationship. These findings suggest that enhancing farmers’ capacity through non-formal education, strengthening the social environment, and optimizing land use can increase motivation and productivity in sweet corn cultivation. The study’s implications highlight the importance of sustainable mentoring programs, improved access to training, and government support in developing sweet corn farming to promote the improvement of farmers’ welfare in Senggi Sub-district.